UPAYA PREVENTIF SATPOL PP/WILAYATUL HISBAH DALAM PENCEGAHAN PELANGGARAN SYARIAT ISLAM DI KOTA BANDA ACEH - Alia Nursaifa; Ruslan; Yusrijal Abdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sharia violations remain a persistent problem in Banda Aceh City despite various preventive measures undertaken by the Civil Service Police Unit and Wilayatul Hisbah (Satpol PP/WH). Violations such as improper dress, ikhtilat, and khalwat continue to occur in public spaces. This study aims to analyze the preventive efforts undertaken by Satpol PP/WH, identify the challenges faced in their implementation, and examine public perceptions of these efforts. A qualitative approach with a descriptive design was employed, with data collected through in-depth interviews and documentation involving Satpol PP/WH officials and community members, then analyzed through data reduction, data display, and conclusion drawing. The findings show that preventive efforts were carried out through routine patrols, socialization, education, guidance, and persuasive approaches, supported by cooperation with religious and community leaders and social media platforms. However, these efforts continue to face internal challenges such as limited personnel, facilities, and budget, and external challenges such as low public legal awareness, social and technological influence, and weak family supervision. The public generally perceives these efforts positively, considering them effective in raising awareness and reducing violations, although supervision in peripheral areas is regarded as insufficient. The study concludes that the effectiveness of sharia enforcement depends not only on legal structure and substance but also on the legal culture of the community, in line with Friedman's Legal System Theory and Hirschi's Social Control Theory. It is recommended that Satpol PP/WH strengthen continuous socialization and community guidance, that the local government provide adequate resources, and that families and communities take a more active supervisory role.